Effect of an activated sludge wastewater treatment plant on ambient air densities of aerosols containing bacteria and viruses. - Fannin, K F (1985)
Bacteria- and virus-containing aerosols were studied during the late summer and fall seasons in a midwestern suburb of the United States before and during the start-up and operation of an unenclosed activated sludge wastewater treatment plant. The study showed that the air in this suburban area contained low-level densities of indicator microorganisms. After the plant began operating, the densities of total aerobic bacteria-containing particles, standard plate count bacteria, total coliforms, fecal coliforms, fecal streptococci, and coliphages increased significantly in the air within the perimeter of the plant. Before plant operations, bacteria were detected from five genera, Klebsiella, Enterobacter, Serratia, Salmonella, and Aeromonas. During plant operations, the number of genera identified increased to 11. In addition to those genera found before plant operations, Escherichia, Providencia, Citrobacter, Acinetobacter, Pasteurella, and Proteus, were also identified. Enteric viruses were detected in low densities from the air emissions of this plant. Only standard plate count bacteria remained at significantly higher than base-line densities beyond 250 m downwind from the center of the aeration tanks. Fecal streptococci and coliphages appeared to be more stable in aerosols than the other indicator microorganisms studied. In general, the densities of microorganism-containing aerosols were higher at night than during the day. The techniques used in this study may be employed to establish microorganism-containing aerosol exposure during epidemiological investigations.